(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The translation of idiomatic expressions poses a major challenge in literary translation due to the complex interplay between linguistic form and cultural context. This article investigates theoretical approaches and practical strategies for the adequate transmission of idiomatic expressions, with a specific focus on the English translation of the Uzbek classic novel “Bygone days” by Abdulla Qodiriy, translated by Mark Reese. Through a comparative analysis, the paper explores the types of phraseological units in the source text, their semantic and stylistic functions, and the adequacy of their equivalents in the target text. The study utilizes V.N. Komissarov’s theory of equivalence to evaluate translation adequacy, and it aims to offer insight into the strategies used by the translator in preserving the cultural and expressive richness of the original text.